2021
DOI: 10.1016/j.jhep.2020.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cardiac dysfunction in intrahepatic cholestasis of pregnancy is associated with elevated serum bile acid concentrations

Abstract: Background & Aims: Intrahepatic cholestasis of pregnancy (ICP) is associated with an increased risk of stillbirth. This study aimed to assess the relationship between bile acid concentrations and fetal cardiac dysfunction in patients with ICP who were or were not treated with ursodeoxycholic acid (UDCA). Methods: Bile acid profiles and NT-proBNP, a marker of ventricular dysfunction, were assayed in umbilical venous serum from 15 controls and 76 ICP cases (36 untreated, 40 UDCAtreated). Fetal electrocardiogram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 52 publications
(80 reference statements)
3
26
0
1
Order By: Relevance
“…12 There is experimental evidence that ursodeoxycholic acid treatment reduces the impact of pathological processes that are implicated in the causes of stillbirth in women with intrahepatic cholestasis of pregnancy, such as placental vasospasm 24 and fetal arrhythmia (abnormal heart rate variability and the elevation of umbilical venous N-terminal pro-brain natriuretic peptide are associated with elevated maternal and fetal bile acid concentrations). 25,26 However, clinical trials powered to detect alterations in stillbirth rates would require participant numbers that are likely to be unfeasible given the disease prevalence. 27 We therefore aimed to use data from existing literature to examine whether ursodeoxycholic acid affects adverse perinatal outcomes, predominantly stillbirth and preterm birth.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…12 There is experimental evidence that ursodeoxycholic acid treatment reduces the impact of pathological processes that are implicated in the causes of stillbirth in women with intrahepatic cholestasis of pregnancy, such as placental vasospasm 24 and fetal arrhythmia (abnormal heart rate variability and the elevation of umbilical venous N-terminal pro-brain natriuretic peptide are associated with elevated maternal and fetal bile acid concentrations). 25,26 However, clinical trials powered to detect alterations in stillbirth rates would require participant numbers that are likely to be unfeasible given the disease prevalence. 27 We therefore aimed to use data from existing literature to examine whether ursodeoxycholic acid affects adverse perinatal outcomes, predominantly stillbirth and preterm birth.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…Activation of TGR5 by bile acids, or other agonists such as progesterone sulfates, may also play a role in the pruritus associated with ICP (87,93,94). As well as maternal effects, bile acids have been directly implicated in fetal arrhythmias, with fetal PR interval elongation and abnormal calcium dynamics reported (95,96,97,98). FXR function has also been linked to the pathophysiology of ICP.…”
Section: Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 99%
“…During pregnancy, serum bile acids within the fetus are slightly higher than those in the maternal circulation where they are ultimately transferred for excretion [6]. In ICP, the feto-maternal concentration gradient is reversed and is known to increase risk of fetal complications such as stillbirth, spontaneous preterm birth, and vasospasms leading to abnormal electrocardiogram (ECG) findings [7]. In particular, it has been shown that fetal cardiomyocytes have increased susceptibility to and incidence of tachycardia, bradycardia, atrial flutter, and supraventricular tachycardia when exposed to elevated bile acids [8].…”
Section: Introductionmentioning
confidence: 99%